SEGURANÇA CIBERNÉTICA PARA DISPOSITIVOS MÓVEIS (REMUNOM, 2024)
Wi-Fi is a wireless connection that offers advantages such as eliminating cabling and making it easier to connect to other devices compatible with this technology. In addition, the use of hotspots provides improved access control and strengthens security. However, a problem was identified in which users face difficulties accessing the wireless network due to the use of the WPA authentication method with a default password, resulting in an inadequate level of security and a lack of access control by administrators. An analysis of the network structure revealed the absence of effective access control, leading to the decision to implement a hotspot deployment project. The results of this analysis confirmed that, despite technological advances, information security on mobile devices in this context still depends a lot on the user.